HIV/AIDS, SARS, and COVID-19: the trajectory of China's pandemic responses and its changing politics in a contested world - Yanqiu Rachel Zhou (BMC, 2024)
Abstract The COVID-19 pandemic has revealed the contested politics of global health governance, though we still don't know enough about the dynamics of domestic pandemic responses, or about the relationship between the politics of those responses and the politics of global health governance, both of which have changed significantly in recent decades. Focusing on three cases (HIV/AIDS, SARS, and COVID-19) of cross-border infectious diseases, this article explores the trajectory of China's pandemic responses in the context of globalization. Attending to changing politics at domestic, international, and global levels, I argue that those responses have been a complex combination of China's domestic politics (e.g., priorities, institutions, leadership, and timing), its international relations (especially with the US), and its engagements with global health governance. It is concluded that the increasing divergence of pandemic responses in a time of ubiquitous global health crisis demands urgent attention to the connections (including contestations) between domestic pandemic responses and the evolvement of global health governance from a broader perspective that considers changes in geopolitics.